Alkali + cellulase-extracted citrus pectins exhibit compact conformation and good fermentation properties. (November 2020) - Cui, Jiefen; Zhao, Chengying; Zhao, Shaojie; Tian, Guifang; Wang, Feng; Li, Chunhong; Wang, Fengzhong; Zheng, Jinkai
Abstract: Citrus pectins are plant cell wall polysaccharides that can be fermented by gut microbiota, which provide beneficial effects for the host through production of short chain fatty acids (SCFAs). The objective of this study was to investigate the relationship between extraction methods (acid, alkali, cellulase, acid + cellulase, and alkali + cellulase), structural characteristics (primary structure and conformation), and in vitro fermentability of orange and grapefruit pectins. We found that alkali + cellulose (P 10  + C )-extracted orange pectin exhibited high yield (25.63%), compact conformation, and favorable fermentation properties. Based on small angle X-ray scattering (SAXS) analysis, P 10  + C pectin exhibited a compact conformation (Dmax, 15 nm) with a small Rg (7.70 nm) and large Rc (4.78 nm), which facilitated SCFA production and promoted beneficial bacteria ( Bifidobacterium and Faecalibacterium ) in an in vitro fermentability evaluation. P 10  + C grapefruit pectin also showed good fermentability, although not as good as that of orange pectin. These results demonstrated that the spatial conformation played a very important role in the in vitro fermentability of the extracted pectins. This study would provide new insights into the extraction-structure-fermentability relationship and will aid the food industry in extracting pectin more efficiently and exploiting novel prebiotics for shaping a balanced gut microbiota and promoting host health. Graphical abstract: Image 1 Highlights: 5 extraction methods of orange and grapefruit pectins were systematically studied. The extraction-structure-fermentability relationship was carefully investigated. Alkali + cellulase-extracted citrus pectin showed the best yield and fermentability. Compact conformation (small Dmax and Rg, large Rc) contributed to fermentability. Conformation played a very important role in the in vitro fermentability of pectin.